Implementasi Standar Pelayanan Minimal (SPM) Penanggulangan Bencana Kebakaran Pada Dinas Pemadam Kebakaran Dan Penanggulangan Bencana Kota Makassar (Jurnal Ekonomi Bisnis dan Akuntansi, 2023)
This research aims to find out how the Minimum Service Standards (SPM) for Fire Disaster Management are implemented in the Makassar City Fire Department. This type of research uses a qualitative descriptive method, namely research that aims to provide an overview of the Implementation of Minimum Service Standards (SPM) for Fire Disaster Management in the Fire Service. Makassar City Fire where the author used the interview method. Data sources consist of primary data obtained through interviews, while secondary data is obtained from documents, notes, modules, official Wikipedia which can be supported by complete primary data. The results of research conducted at the Makassar City Fire Department Office, in the Implementation of Minimum Service Standards (Spm) for Fire Disaster Management, there are criteria, namely: How to Implement Minimum Service Standards (Spm) for Fire Disaster Management at the Makassar City Fire Department and Factors Inhibiting the Implementation of Service Standards Minimum (SPM). Based on the results of this research, it shows that the implementation of the Minimum Service Standards (Spm) for Fire Disaster Management at the Makassar City Fire Department has been carried out quite well and is in accordance with the achievements of the Minimum Service Standards at the Makassar City Fire Department, although there are still several inhibiting factors, but the attitude of responsibility of each member/employee of the Makasssar city fire department continues to be carried out.